Relaxation‐corrected macromolecular model enables determination of 1H longitudinal T1‐relaxation times and concentrations of human brain metabolites at 9.4T. Issue 1 (10th August 2021) - Wright, Andrew Martin; Murali‐Manohar, Saipavitra; Borbath, Tamas; Avdievich, Nikolai I.; Henning, Anke
Abstract : Purpose: Ultrahigh field MRS has improved characterization of the neurochemical profile. To compare results obtained at 9.4T to those from lower field strengths, it is of interest to quantify the concentrations of metabolites measured. Thus, measuring T1 ‐relaxation times is necessary to correct for T1 ‐weighting that occurs in acquisitions for single‐voxel spectroscopy and spectroscopic imaging. A macromolecule (MM) simulation model was developed to fit MM contributions to the short TE inversion series used to measure T1 ‐relaxation times. Methods: An inversion series with seven time points was acquired with metabolite‐cycled STEAM to estimate T1 ‐relaxation times of metabolites. A short TE was employed in this study to retain signals from metabolites with short T2 ‐relaxation times and J‐couplings. The underlying macromolecule spectrum was corrected by developing a sequence‐specific, relaxation‐corrected simulated MM model. Quantification of metabolite peaks was performed using internal water referencing and relaxation corrections. Results: T1 ‐relaxation times for metabolites range from approximately 750 to approximately 2000 ms and approximately 1000 to approximately 2400 ms in gray matter (GM)‐ and white matter (WM)‐ rich voxels, respectively. Quantification of metabolites was compared between GM and WM voxels, as well as between results that used a simulated MM spectrum against those that used an experimentally acquired MM spectrum. Metabolite concentrations are reported in mmol/kg quantities. Conclusion: T1 ‐relaxation times are reported for nonsinglet resonances for the first time at 9.4T by use of a MM simulation model to account for contributions from the MM spectrum. In addition to T1 ‐relaxation times, quantification results of metabolites from GM‐ and WM‐rich voxels are reported.